"Two-Eyed Seeing": Moving from Paralysis to Action in Understanding the Legacy of Indian Residential Schools in British Columbia, Canada. Issue 3 (3rd July 2017) - Kay, Cheryl
ABSTRACT: This article documents a reflexive personal teacher narrative (Brookfield 1995; Cochran-Smith and Lytle 2009; Humphreys 2005; Hamilton, Smith, and Worthington 2009; Larrivee 2010) about understanding the legacy of the Indian Residential School experience for indigenous people of British Columbia, Canada. In 2015, a new curriculum was introduced. I felt curiously ill-prepared to use my skill set as an experienced dance educator to build awareness about this issue. Empowered by the idea of "two-eyed seeing" explained by Mi'kmaw Elder Albert Marshall, which acknowledges two sides to the healing process, I began to move forward. Through a process of artistic introspection, circular reflection, and collegial collaboration, I was able to reposition myself so that I better understood the issues involved and my stance within them. Knowing that dance is not well understood for its place in education, I recall this journey so other dance educators and teachers can also move beyond paralysis to action.